Flavoring Production in Kamut®, Quinoa and Wheat Doughs Fermented by Lactobacillus paracasei, Lactobacillus plantarum, and Lactobacillus brevis: A SPME-GC/MS Study - Di Renzo, Tiziana; Reale, Anna; Boscaino, Floriana; Messia, Maria C. (Frontiers in Microbiology, 2018)
This study identified the odor-active compounds and the qualitative characteristics of doughs from “ancient” grains flours fermented by lactic acid bacteria. For this purpose doughs made with quinoa and Kamut® flours have been produced and inoculated with strains belonging to the species Lactobacillus paracasei, Lactobacillus plantarum and Lactobacillus brevis and compared with fermented doughs made from 100% wheat flour. The quality of the doughs was determined by assessment of pH, total titratable acidity, lactic acid bacteria growth and flavor compounds. The results showed that lactic acid bacteria used were able to grow in the different substrates reaching more than 9.0 log CFU/g after 24 h fermentation, although the best microbial growth was recorded in the doughs made with quinoa flour fermented with Lactobacillus paracasei I1. Good acidification and heterogeneous aromatic profile were recognized in all the doughs even if the volatile composition mainly derived from microbial specie. Among all the used strains, mostly Lactobacillus paracasei I1 positively contributed to the aromatic profile of the doughs, independently from flour type, producing the highest amount of different ketones such as, diacetyl, acetoin, 2,6-dimethyl-4-heptanone, 5-methyl-3-hexanone, 4-methyl-3-penten-2-one, volatile compounds highly appreciated in the bakery products for their buttery, fatty and fruity notes. So, the positive characteristic of Lactobacillus paracasei I1 to enhance the production of desired volatile compounds could make it suitable as adjunct culture starter in the bakery industry. Many differences in volatile organic compounds derived also by the type of flour used. Quinoa fermented doughs were characterized for specific nutty, roasted, acid and buttery tones derived from pyrazines, ketones and acid compounds whereas Kamut® fermented doughs were characterized for fruity, rose, green and sweet tones derived from aldehydes and ketones production. So, the use of quinoa and Kamut® flours opportunely fermented, as partial or complete substitution of wheat flour, may be interesting for producing more balanced bakery products with respect to nutritional aspects and to unique aromatic profile. Furthermore, the supplementation of these flours, rich in protein content and free amino acids, could represent an optimal substrate to enhance the growth of lactic acid bacteria used as starter culture in leavened bakery products.